Chronic disease multimorbidity among the Canadian population: prevalence and associated lifestyle factors - Nigatu Regassa Geda; Bonnie Janzen; Punam Pahwa (BMC, 2021)
Abstract Background Chronic diseases is increasingly becoming one of the most pressing public health concerns in most part of the world, including the Canadian population. The purpose of this study was to estimate the prevalence of multimorbidity in the general population based on 14 major chronic diseases and examine associations with lifestyle/behavioral factors. Methods The data source was the 2015-2016 Canadian Community Health Survey (CCHS). The CCHS is a cross sectional, complex multi-stage survey based on information collected from 109,659 participants aged 12+, covering all provinces and territories. Multimorbidity was defined as the co-occurrence of two or more chronic diseases within a person. Multiple logistic regression was used to examine the key determinants of multimorbidity. Results The prevalence of multimorbidity was 33 %. Adjusting for sociodemographic variables, there was an increased odd of multimorbidity for those having a sedentary lifestyle (AOR = 1.06; CI:1.01-1.11) and being obese (AOR = 1.37; CI:1.32-1.43) or overweight (AOR = 2.65; CI: 2.54-2.76). There were two statistically significant interactions, between sex and smoking, and between immigration status and alcohol intake. Smoking was more strongly associated with multimorbidity in females than males. The association between alcohol intake and multimorbidity was also dependent upon immigration status. Conclusions Given the high prevalence of multimorbidity among the general Canadian population, policy makers and service providers should give more attention to the behavioral/lifestyle factors which significantly predicted multimorbidity. Policy and program efforts that promote a healthy lifestyle should be a priority.